2001
DOI: 10.1093/ndt/16.5.1024
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal tuberculosis in patients receiving continuous ambulatory peritoneal dialysis

Abstract: Peritoneal TB, whilst otherwise relatively uncommon, is an important manifestation of TB in CAPD patients and usually develops soon after commencing dialysis. The reasons for this are unknown and require further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Most studies have shown a predominance of extrapulmonary TB in dialysis patients [10][11][12] and this was also the case in this series. Peritoneal TB, otherwise relatively uncommon and which occurred in eight of 14 (57%) of the CAPD patients in this study, is the subject of a separate paper [13]. The other main extrapulmonary site was lymph nodes that were affected in six patients, all on dialysis.…”
Section: Discussionmentioning
confidence: 60%
“…Most studies have shown a predominance of extrapulmonary TB in dialysis patients [10][11][12] and this was also the case in this series. Peritoneal TB, otherwise relatively uncommon and which occurred in eight of 14 (57%) of the CAPD patients in this study, is the subject of a separate paper [13]. The other main extrapulmonary site was lymph nodes that were affected in six patients, all on dialysis.…”
Section: Discussionmentioning
confidence: 60%
“…A lymphocyte or monocyte pleocytosis has been reported in several cases of PD tuberculous peritonitis and is a consistent finding in non-PD tuberculous peritonitis patients [3,4,10,13]. AFB smears were frequently negative [4,7,10,11,12] and mycobacterium was cultured from the effluent in only 0%-79% of cases [4,7,8,10,11,12]. Because it is a slow-growing and fastidious organism, mycobacterium requires special media for growth and culture for a prolonged period of time.…”
Section: Discussionmentioning
confidence: 92%
“…Other reported presentations included Tenckhoff catheter failure, paraplegia from a spinal abscess, relapsing peritonitis, and bone pain from TB osteomyelitis [2,7,8,9]. In two case series evaluating tuberculous peritonitis in nondialysis-dependent as well as PD-dependent patients, presenting signs and symptoms were abdominal distention and ascites, fever, weight loss, and abdominal pain [4,7,10,11,12] (Table 1). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, patients on peritoneal dialysis who are at risk of intra -abdominal infection also require special consideration. 9,21 A chest radiograph should be performed as part of the workup of all renal patients to show any evidence of previous TB disease, but also so that future radiographs can be compared with previous studies, and any new infiltrates warrant further investigation. Further site -specific investigations such as abdominal ultrasound, computed tomography, or spinal magnetic resonance imaging should be considered based on symptoms.…”
Section: Tuberculin Skin Testmentioning
confidence: 99%